GAD2 on chromosome 10p12 is a candidate gene for human obesity. - Philippe Boutin; Christian Dina; Francis Vasseur; Séverine Dubois; Laetitia Corset; Karin Séron; Lynn Bekris; Janice Cabellon; Bernadette Neve; Valérie Vasseur-Delannoy; Mohamed Chikri; M Aline Charles; et al. (PLoS Biology)
The gene GAD2 encoding the glutamic acid decarboxylase enzyme (GAD65) is a positional candidate gene for obesity on Chromosome 10p11-12, a susceptibility locus for morbid obesity in four independent ethnic populations. GAD65 catalyzes the formation of gamma-aminobutyric acid (GABA), which interacts with neuropeptide Y in the paraventricular nucleus to contribute to stimulate food intake. A case-control study (575 morbidly obese and 646 control subjects) analyzing GAD2 variants identified both a protective haplotype, including the most frequent alleles of single nucleotide polymorphisms (SNPs) +61450 C>A and +83897 T>A (OR = 0.81, 95% CI [0.681-0.972], p = 0.0049) and an at-risk SNP (-243 A>G) for morbid obesity (OR = 1.3, 95% CI [1.053-1.585], p = 0.014). Furthermore, familial-based analyses confirmed the association with the obesity of SNP +61450 C>A and +83897 T>A haplotype (chi(2) = 7.637, p = 0.02). In the murine insulinoma cell line betaTC3, the G at-risk allele of SNP -243 A>G increased six times GAD2 promoter activity (p < 0.0001) and induced a 6-fold higher affinity for nuclear extracts. The -243 A>G SNP was associated with higher hunger scores (p = 0.007) and disinhibition scores (p = 0.028), as assessed by the Stunkard Three-Factor Eating Questionnaire. As GAD2 is highly expressed in pancreatic beta cells, we analyzed GAD65 antibody level as a marker of beta-cell activity and of insulin secretion. In the control group, -243 A>G, +61450 C>A, and +83897 T>A SNPs were associated with lower GAD65 autoantibody levels (p values of 0.003, 0.047, and 0.006, respectively). SNP +83897 T>A was associated with lower fasting insulin and insulin secretion, as assessed by the HOMA-B% homeostasis model of beta-cell function (p = 0.009 and 0.01, respectively). These data support the hypothesis of the orexigenic effect of GABA in humans and of a contribution of genes involved in GABA metabolism in the modulation of food intake and in the development of morbid obesity.